2018
DOI: 10.1515/msr-2018-0010
|View full text |Cite
|
Sign up to set email alerts
|

High Precision Edge Detection Algorithm for Mechanical Parts

Abstract: High precision and high efficiency measurement is becoming an imperative requirement for a lot of mechanical parts. So in this study, a subpixel-level edge detection algorithm based on the Gaussian integral model is proposed. For this purpose, the step edge normal section line Gaussian integral model of the backlight image is constructed, combined with the point spread function and the single step model. Then gray value of discrete points on the normal section line of pixel edge is calculated by surface interp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 13 publications
1
15
0
Order By: Relevance
“…A precision analysis of the effect of kernel sizes and sampling interval has initially quantified the limits of operation for the method in real optical systems. The demonstrated accuracies for the investigations in References 23‐26 and32,33 have reinforced the potential application, of this initial study, in digital correlation and deformation measurement driven by planar features at the millimeter and micrometer scale. In comparison to the popular subpixel edge detection method, based on spatial moments, 5 the authors show a consistent measurement sensitivity of order 10 −6 perturbed by speckle and Gaussian noise with a runtime of 0.004 second for a 11 × 11 region.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…A precision analysis of the effect of kernel sizes and sampling interval has initially quantified the limits of operation for the method in real optical systems. The demonstrated accuracies for the investigations in References 23‐26 and32,33 have reinforced the potential application, of this initial study, in digital correlation and deformation measurement driven by planar features at the millimeter and micrometer scale. In comparison to the popular subpixel edge detection method, based on spatial moments, 5 the authors show a consistent measurement sensitivity of order 10 −6 perturbed by speckle and Gaussian noise with a runtime of 0.004 second for a 11 × 11 region.…”
Section: Discussionsupporting
confidence: 58%
“…Applications that we envisage the proposed method may be useful for are the accurate registration between two images, nonrigid/rigid body measurements and defect detection. [23][24][25][26] In Reference 25, the authors demonstrated the use of digital correlation to investigate localized thermal deformation within semiconductor devices. It was shown that minimizing alignment errors between images was a crucial preprocessing step before applying correlation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Bresenham algorithm, the active pixel moves one unit with every frequency change along the principal direction. e secondary directional movement is determined by the midpoint deviation discrimination [13,14]. e starting point of the ideal line is defined as P 0 (x 0 , y 0 ), and the ending point is defined as P n (x n , y n ).…”
Section: Principle Of Bresenham Algorithmmentioning
confidence: 99%
“…The bearings support the spindle during rotation and sustain the forces exerted by the spindle and external loads. The interaction effect between the electromagnetic field and mechanical structure may cause undesired subcritical resonance vibration of the spindle, and high precision and high efficiency measurement is becoming an imperative requirement for the vibration of the spindle [3].…”
Section: Introductionmentioning
confidence: 99%